Analisis Faktor Risiko pada Bayi dengan BBLR di RS Margono Soekarjo Purwokerto - Sumarni Sumarni; Adinda Putri Sari Dewi (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Overview: Low Birth Weight (LBW) is a significant health problem in Indonesia because it is at risk of increasing neonatal mortality and morbidity. Objective: This study aims to analyze the risk factors associated with the incidence of LBW in newborns at Prof. Dr. Margono Soekarjo Purwokerto Hospital. Research Method: The method used is an analytical observational study with a cross-sectional design. A sample of 200 mothers and babies was obtained through purposive sampling techniques. Data were collected from medical records and analyzed using the chi-square test and logistic regression. Research Results: showed that prematurity had a partial effect on LBW with a sig value of 0.000 <0.05, and showed that if the incidence of prematurity increased by one percent, assuming the value of other variables remained constant, it would increase the incidence of LBW by 2.769 percent. Variables parity, maternal age, anemia, twin pregnancy, hydramnios, PEB, Placenta Previa, KPD, prematurity, fetal pregnancy simultaneously affected LBW. Conclusion: parity, maternal age, anemia, twin pregnancy, hydramnios, PEB, Placenta Previa, KPD, prematurity, fetal pregnancy simultaneously affect LBW.